Apollo : the brilliant one - O'Connor, George (2016)
"Mighty Apollo is known by all as the god of the sun, but there's more to this Olympian than a bright smile and a shining chariot"--
"A Neal Porter Book."
Ages 9-14.
Keywords: Apollo -- (Deity) -- Juvenile literature; Gods, Greek -- Juvenile literature; Mythology, Greek -- Juvenile literature